The Impact of Perceived Value & Implementation of Good Governance to Satisfaction (The Study to Lectures at Public University) - Rivaldi Arissaputra; Sarah Sentika (CV. AFDIFAL MAJU BERKAH, 2021)
This research is a study form of perceived value and good governance in the satisfaction of lecturers in state universities. The purpose of this research is to analyze the effect of perceived value and good governance on satisfaction perceived by lecturers who teach in state universities in Bandung where the focus of this case study is the lecturers who teach at Padjadjaran University, the Bandung Institute of technology and the Indonesian University of Education. The survey technique used in data collection is a questionnaire with measurements using a Likert scale. Data collection technique used is purposive sampling with a total of 238 respondents. The analytical method used in this study is carried out using the Structural Equation Modeling (SEM) method with the help of Lisrel 8.24 software and to test the validity and reliability of the construct carried out with SPSS. The results showed that the variables perceived value and good governance affect the satisfaction of the lecturer where good governance has a greater influence than perceived value on lecturer satisfaction.